Collision Alert Using Visible Light Communication - Parimalam, Vinisa; Nan Mad Sahar (Evolution in Electrical and Electronic Engineering, 2023)
The ability to own a vehicle increases the rate of usage on the road. Many accidents occur especially on highways due to the distance of vehicles that are too close to each other. If the driver in front of the car slows down or applies the brakes, the following vehicle driver finds it difficult to manage his car, resulting in a collision. In order to reduce road accidents in Malaysia, a car accident alert system is vital as a warning to the driver before the crash. This system is also important to flatten the curve rate of fatalities in road accidents in Malaysia. This project aims to design vehicle accident alerts by using Visible Light Communication (VLC). As Malaysia is geographically located on the equatorial line and is receiving plenty of sunshine over the years, the VLC Technology is suitable for this system. Therefore, the proposed project is hoped to save the development cost. The project is divided into four main parts comprised of input (distance), microcontroller (Arduino Uno), Li-Fi transmitter and Li-Fi receiver part and output. The microcontroller acts like a brain that reads the input or signal from the Light Dependent Resistors (LDR). Then, the Li-Fi transmitter and Li-Fi receiver will make a data transfer by using light. The microcontroller will operate to activate the buzzer as an alarm alert in this project. Lastly, the performance is evaluated under realistic collision avoidance scenarios. Results demonstrate that the proposed method performs at 10cm level accuracy. The tally in the experiment, 1 cm equals 100 m in the real world. When the final experimental result was compared to the accepted value for the entire experiment’s result, it was discovered that the experiment was perfectly accurate. At the end of this project, the simulation of the collision alerting system was also presented. For future recommendations, the development project may implement an increase in the model training dataset and to develop a proper prototype for vehicles for better performance and better data transmission results.